Pengaruh Fraud Hexagon dan Self Efficacy terhadap Kecurangan Akademik Mahasiswa - Aulia Rahmat; Mia Angelina Setiawan (Universitas Negeri Padang, 2024)
The goal of this research is to investigate how the Fraud Hexagon and a sense of self-efficacy play a role in academic dishonesty among accounting majors at Universitas Negeri Padang. A total of 69 individuals were used to represent the entire population of S1 accounting students at Universitas Negeri Padang in this study. This study used total sampling as method for collecting sample. This research makes use of primary data in the form of google form-distributed questionnaires. Multiple linear regression analysis was performed in this model study. The findings of this study showed that academic fraud among accounting students at Universitas Negeri Padang was unaffected by factors such as peer pressure, perceived competence, arrogance, collusion, or perceived efficacy. This research, however, was able to show that accounting students at Universitas Negeri Padang commit academic fraud because of opportunities and rationalizations.